Thiamine Deficiency M74 Developed in Salmon (Salmo salar) Stocks in Two Baltic Sea Areas after the Hatching of Large Year-Classes of Two Clupeid Species : Detected by Fatty Acid Signature Analysis - Vuorinen, Pekka J.; Käkelä, Reijo; Pakarinen, Tapani; Heinimaa, Petri; Ritvanen, Tiina; Nikonen, Soili; Rokka, Mervi; Keinänen, Marja (Fishes)
Lipid-related thiamine (vitamin B1) deficiency of Baltic salmon (Salmo salar), the M74 syndrome, is generally caused by feeding on abundant young sprat (Sprattus sprattus) in the Baltic Proper, the main foraging area of these salmon. In 2014, a strong year-class of sprat was hatched in the Baltic Proper, and a strong herring (Clupea harengus) year-class was hatched in the Gulf of Bothnia, where herring is the dominant salmon prey. The fatty acid (FA) signatures of prey fish in muscle or eggs of second sea-year spawners suggested that 27% of wild River Simojoki and 68% of reared River Dal salmon remained in the Gulf of Bothnia in 2014 instead of continuing to the Baltic Proper. In 2016, 23% of the M74 females of the River Simojoki and 58% of the River Dal originated from the Gulf of Bothnia, and 13% and 16%, respectively, originated from the Baltic Proper. Some salmon from the River Neris in the southern Baltic Proper had also been feeding in the Gulf of Bothnia. In general, low free thiamine (THIAM) concentration in eggs was associated with high lipid content and high docosahexaenoic acid (DHA, 22:6n−3) and n−3 polyunsaturated FA (n−3 PUFA) concentrations in muscle but not in eggs. A higher THIAM concentration and lower proportions of DHA and n−3 PUFAs in Arctic Ocean salmon eggs, despite higher egg lipid content, indicated that their diet contained fewer fatty fish than the Baltic salmon diet. Hence, M74 originated by foraging heavily on young fatty sprat in the Baltic Proper or herring in the Gulf of Bothnia. 2024